Error Analysis On "Explanation"Text Written By The Third-Grade Students Of Sma Negeri 1 Karanganom-Klaten - Sulasniyati, Sulasniyati (2012)
This research aims at analyzing errors which are made by the third - grade students of SMA NEGERI 1 KARANGANOM, KLATEN in writing essays on 'explanation' text, describing the errors and figuring out the frequency of each type of the errors. This research belongs to descriptive qualitative research. In collecting the data, the writer applies documentation of students' essays. The writer analyzes fourthy four students' worksheets. Their errors are then classified into groups after they are identified. Next, error are analyzed by means of the theory of 'linguistic category taxonomy' and 'surface strategy taxonomy' before finally their frequency is figured out. The frequency of the errors can be summarized as follow ; The errors belong to three main groups ; "Grammatical Construction" with 199 errors or 49.14 %, "Part of Speech" with 141 errors or 34.82 % and "Vocabulary" with 65 errors or 16.05 %. Each group is then further elaborated into divisions. 'Grammatical Construction' is divided into ; Bound Morpheme with 108 errors or 26.67 %, Passive Sentence with 28 error or 6.91 % Noun Phrase with 14 errors or 3.46 %, Modal with 1 error or 0.25 %. Be with 32 errors or 7.90 %, Substituting verb with 5 errors or 1.24 %, Omission of Subject with 6 errors or 1.48 %, Addition of Subject with 1 error or 0.25 %, concord with 4 errors or 0.99 %. 'Part of Speech' consists of : verb with 51 errors or 12.59 %, 'Preposition' with 40 errors or 9.88 % 'Article' with 20 errors or 4.94 %, 'Adjective' with 10 errors or 2.47 %, 'Pronoun' with 9 errors or 2.22 %, 'Adverb' with 5 errors or 1.24 %, 'Noun' with 3 errors or 0.75 %.and 'Conjuction' with 3 errors or 0.75 %. 'Vocabulary' consists of : False Friend ; 'Similar in Meaning' with 27 errors or 6.67 %, 'Similar in Form' with 20 errors or 4.94 % and 'Literal Translation' with 18 errors or 4.44 %. Under the source of errors, there are two kinds, those are ; errors caused by interlingual transfer consist of 116 or 54.98 % and errors caused by intralingual transfer consist of 95 or 45.02 %. The error analysis in this research is expected to be beneficial for English teachers in determining which point of the teaching material that should be given more emphasis.